Role of Oral Microbiota as Predictive Biomarkers for Radiation-Induced Toxicities. - Prince Prakash; Meher Surjya Shankar; Paikray Rajlaxmi; Ayesha Sitam; Ray Suparna Ghosh (Student's Journal of Health Research Africa, 2026)
Background:Radiotherapy for head and neck cancers commonly causes oral toxicities that can affect treatment tolerance and quality of life. Alterations in oral microbiota may help identify patients at increased risk of these complications. Methods:A retrospective observational study was conducted at Burdwan Medical College and Hospital between June 2024 and July 2025. Medical records of 79 patients with histologically confirmed head and neck cancer who completed definitive radiotherapy, with or without concurrent chemotherapy, were reviewed. Demographic characteristics, clinical parameters, treatment details, oral microbiological findings, and radiation-induced toxicities graded according to the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0 were retrieved. Associations between microbial profiles and treatment-related toxicities were analyzed using chi-square test, Student's t-test, and multivariate logistic regression. Statistical significance was considered at p <0.05. Results:Among 79 patients, 53.2% developed Grade II–III oral mucositis, while xerostomia and oral candidiasis occurred in 44.3% and 27.8% of patients, respectively. Patients demonstrating higher baseline colonization with Candida species and pathogenic Gram-negative bacteria experienced significantly greater rates of severe mucositis and xerostomia (p<0.05). Reduced abundance of commensal Streptococcus species was independently associated with increased radiation-induced toxicity. Multivariate analysis identified baseline dysbiosis as an independent predictor of Grade II–III mucositis (adjusted OR 3.42, 95% CI 1.48–7.92, p=0.003). Conclusion:Baseline oral microbial dysbiosis was associated with radiation-induced oral toxicities and may help identify patients at increased risk of severe treatment-related complications. Recommendation:Prospective multicenter studies incorporating microbiome sequencing and longitudinal microbial profiling are recommended to validate these findings and support the development of microbiota-based preventive strategies.